2022
DOI: 10.1186/s12348-022-00311-4
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal vein occlusion post ChAdOx1 nCoV-19 vaccination – can it be explained by the two-hit hypothesis?

Abstract: Purpose To report a case of central retinal vein occlusion (CRVO) seven days following the first dose of ChAdOx1 nCoV-19 vaccine and propose a hypothesis for the possible underlying pathogenesis. Observation A 31-year-old male presented with CRVO with cystoid macular edema, one week after receiving his first ChAdOx1 nCoV-19 vaccine dose. Apart from mild hyperhomocysteinemia, no major thrombophilic or systemic risk factors were found. Anti-platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… 35 , 38 A study by Parakh et al, suggested that the COVID-19 vaccine might trigger venous thromboembolism in background homocysteinemia and might have a potential effect on endothelial cells and autoimmunity. 36 However, the hypothesis was still doubtful because of the weak or unclear association of homocysteine and venous thromboembolic events and the effectivity of the homocysteine-lowering drugs in reducing the risk of venous thromboembolic events. It was also hypothesized by Leung et al, that the COVID-19 vaccine can induce inflammation in retinal vasculature and will induce thromboembolic events, and has been observed for other types of vaccination like influenza, although it was also still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 , 38 A study by Parakh et al, suggested that the COVID-19 vaccine might trigger venous thromboembolism in background homocysteinemia and might have a potential effect on endothelial cells and autoimmunity. 36 However, the hypothesis was still doubtful because of the weak or unclear association of homocysteine and venous thromboembolic events and the effectivity of the homocysteine-lowering drugs in reducing the risk of venous thromboembolic events. It was also hypothesized by Leung et al, that the COVID-19 vaccine can induce inflammation in retinal vasculature and will induce thromboembolic events, and has been observed for other types of vaccination like influenza, although it was also still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The result was different from previous studies which stated that BRVO was more common than CRVO. 17 , 57 However, if we looked at each group, BRVO was the most diagnosed in the mRNA vaccine group with 16 cases (20.51%) [case #6–7, 18–19, 26, 28–29, 33–34, 36, 63, 66, 69–70, 73–74], 28 , 37 , 38 , 44 , 46–48 , 52 , 53 tied with CRVO with 16 cases (20.51%) [case #1–3, 5, 10, 15–16, 21, 27, 30, 49, 53–54, 64, 67–68], 23–25 , 27 , 30 , 34 , 35 , 40 , 45 , 47 , 50–53 while in the viral vector vaccine group, 14 cases (17.95%) were diagnosed with CRVO [case #8–9, 11, 13, 17, 20, 23–25, 52, 59, 71, 76–77], 29 , 31 , 32 , 36 , 39 , 42 , 43 , 51 , 53 and 13 cases (16.67%) were diagnosed with BRVO [case #12, 14, 31–32, 48, 55–58, 60, 62, 65, 72]. 32 , 33 , 47 , 50–53 …”
Section: Discussionmentioning
confidence: 99%
“…One patient had mildly raised inflammatory markers (erythrocyte sedimentation rate (ESR): 49, C-reactive protein (CRP): 14.6—unit not provided), rheumatoid factors (11, unit not provided) and d-dimer (6077.4 ng/mL) [ 8 ]. A mildly elevated homocysteine level was reported in two cases (16.4 and 22.19 micromol/L) [ 9 , 10 ]. Elevated lipid levels (total cholesterol: 227; LDL: 159, unit not provided) and mildly raised ESR (26, unit not provided) were detected from a case of combined CRAO and RVO [ 11 ].…”
Section: Clinical Characteristics Of Rvo Following Covid-19 Vaccinationmentioning
confidence: 99%
“…Nonetheless, the measurement of the anti-PF4 antibody level was only reported in five cases and no positive tests were reported [ 9 , 10 , 32 ]. That said, no conclusion on the effect of this phenomenon on post-vaccination RVO can be made based on the negative finding in just a few cases.…”
Section: Proposed Mechanisms Of Suspected Vaccine-related Rvomentioning
confidence: 99%
See 1 more Smart Citation